Perancangan Sistem Informasi E-Commerce Berbasis Web pada UMKM Stretto Pizza - Theresia Rosyelani Nena; Ferdinandus Lidang Witi; Elvira Esperanza Sala (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
Advances in information technology have brought significant changes to how Micro, Small, and Medium Enterprises (MSMEs) conduct their business operations, particularly in the areas of marketing and sales. However, Stretto Pizza MSME still relies on manual processes for ordering and transaction recording, which results in limited marketing reach, suboptimal data management, and an increased risk of errors in recording. This study aims to develop a web-based e-commerce information system that can integrate sales processes and data management more effectively. System development was conducted using the Waterfall method, which includes the stages of requirements analysis, design, implementation, testing, and maintenance. The system was built using the PHP programming language with MySQL database support. System testing was performed using the Black-Box Testing method to ensure that every feature functions according to user needs. The research results show that the designed system is capable of supporting product ordering processes, customer data management, sales transactions, and report generation more efficiently. With this system, it is hoped that the Stretto Piza SME can improve its operations while expanding its marketing reach through the use of digital technology.